Assessing the acute differential toxicity of polystyrene microplastic particles and comparing the impacts of bead-shaped versus fragmented particles on Daphnia magna - Sang-Ah Lee; Maranda Esterhuizen; Youngsam Kim; Minsik Kim; Young Jun Kim (Applied Biological Chemistry)
Abstract This study investigates polystyrene (PS) microplastics impact on the freshwater crustacean Daphnia magna, a sentinel species for environmental monitoring. Rather than utilizing their commercial microplastic counterparts, realistic microplastic morphologies that mimic those found in natural aquatic ecosystems were used to assess the hazard PS particles pose to aquatic organisms. A comprehensive suite of biological endpoints, including immobilization rates, generation of reactive oxygen species (ROS), expression levels of ROS-related genes and wide-ranging transcriptomic profiling, was encompassed in our methodology. This study, through these multifaceted experimental approaches, aimed to elucidate the detrimental effects of PS exposure on the early life stages of D. magna, i.e., neonates, with an emphasis on oxidative stress. The EC10 (effective concentration for 10% of the population) of ground PS (G-PS, fragments) was lower than that of purchased PS (C-PS, beads) in the immobilization test, resulting in the complete daphnid mortality. To advance the mechanistic understanding of microplastic-induced stress responses, a key goal was to integrate transcriptomic data with gene expression patterns. Daphnids exposed to PS fragments increased their oxidative stress response genes. However, in those exposed to PS beads, oxidative stress-related genes were not found in the top-10 expression of cellular components from the transcriptome. By illuminating the molecular responses induced by different shapes of microplastics in D. magna, the results of this research significantly expand the knowledge of microplastic impacts on aquatic ecosystem. We aim to provide insights into the ecological risks associated with microplastic pollution by understanding how varying shapes of microplastics affect this keystone species. Graphical Abstract